Analisis Yuridis Terhadap Pemungutan Pajak Pertambahan Nilai atas Penjualan Emas Perhiasan di Kota Samarinda - Huriadana, Asra; Susanti, Erna; Hediati, Febri Noor (Jurnal Ilmiah Advokasi, 2025)
The Value Added Tax (VAT) on gold jewelry requires merchants to calculate, deposit, and report the amount of tax payable independently (self-assessment) in accordance with prevailing tax regulations. However, in Samarinda City, several gold shops have yet to comply with this obligation. This study employs a non-doctrinal/empirical approach using both primary and secondary data. The research focuses on the inhibiting factors in the collection of VAT on gold jewelry sales and its legal implications. The findings reveal that the main obstacles are the low participation of taxpayers due to limited awareness of taxation obligations related to gold jewelry as a taxable object, as well as weak systems of recording and monitoring the number of gold shops subject to tax. From the law enforcement perspective, the lack of time and human resources among tax officials further hampers the optimization of VAT collection. These findings highlight the necessity of improving taxpayer awareness, strengthening monitoring systems, and enhancing the capacity of tax authorities to ensure the effectiveness of VAT collection on gold jewelry sales in Samarinda City.Keywords: Implications; Value Added Tax; Jewelry